Effect of melatonin on otoprotection in rodents: a systematic review with meta-analysis - Assumpção, Natália Lombardi (2023)
Objectives: To determinate the otoprotective efficacy of melatonin.in experimental models of rodents through a systematic review of the literature. Methods: Altogether, 154 articles were found in four databases. The PICOS strategy (Population, Intervention, Comparison, and Outcome) was used to define the eligibility criteria. Studies that met the inclusion criteria for the second step were included in a qualitative synthesis. Each study type was analyzed with the CAMARADES quality of assessment’s checklist end the SYRCLE RoBS risk of bias. Results: Seven articles were selected, and four were included in the meta-analysis. It was possible to obtain seven outcomes according to the standard auditory frequencies presented among the studies, considering a minimum of three standard frequencies. The outcomes analyzed were for the frequencies of 1500, 2000, 3000, 4000, 5000, 6000, and 8000 Hz.